Effects of mycotoxin adsorbents in aflatoxin B 1 - and fumonisin B 1 -contaminated broiler diet on performance and blood metabolite - Sobrane Filho,Sérgio Turra (2016)
ABSTRACT The present study examined the effect of aflatoxin (AFB1) and fumonisin (FB1) at the levels of 2 mg kg−1 AFB1 and 100 mg kg−1 FB1 and the efficiency of use of different levels of adsorbent based on sodium and calcium aluminosilicate on growth performance, hematological parameters, and biochemical parameters of broilers. A total of 1,440 Cobb broilers were distributed into the following treatments: positive control (PC) - no mycotoxin and adsorbent (AD); PC+3AD - no mycotoxin, with 3 g kg−1 adsorbent in feed; negative control (NC) - only mycotoxin; NC+1AD - with mycotoxin and 1 g kg−1 adsorbent in feed; NC+2AD - with mycotoxin and 2 g kg−1 adsorbent in feed; and NC+3AD - with mycotoxin and 3 g kg−1 adsorbent in feed. The amounts of AFB1 and FB1 added to NC reduced weight gain (35%) and feed intake (50%) compared with PC; however, inclusion of 2 or 3 g kg−1 adsorbent to NC alleviated such losses. Birds fed NC showed anemia, immunosuppression, and impaired liver function, observed by reduced cholesterol and increased gamma glutamyl-transferase activity compared with PC; values returned to normal levels when 2 or 3 g kg−1 of the adsorbent (as fed) were used. Mycotoxins cause adverse effects on most of the parameters studied, and the use of adsorbent at the levels of 2 and 3 g kg−1 of the adsorbent as fed partially negates the adverse effect of mycotoxicosis.